SYNTHESIS OF NEW 10-SUBSTITUTED PHENOTHIAZINES AS ANTIINFLAMMATORY AND ANALGESIC AGENTS. - Upendra Kumar Kushwaha,; Yashovardhan,; Sudhir Kumar Bhati,; Ashok Kumar, (International Journal of Pharma and Bio Sciences, 2010)
Some new 2-chloro-10-[2-{3'-chloro-2'-oxo-4'-(substitutedphenyl)1'-azetidinyl} thiazol-4-yl] phenothiazines (4a-4g) and 2-chloro-10-[2-{3'-chloro-2'-oxo-4'-(substitutedphenyl)1'azetidinyl}oxazol-4-yl] phenothiazines (4a'-4g') have been synthesized from 2-chloro-10-[2(substitutedphenyl) methylene aminothiazol-4-yl] phenothiazines (3a-3g) and 2-chloro-10-[2(substituted phenyl) methylene aminooxazol -4-yl] phenothiazines (3a'-3g') respectively. The structures of all these compounds were established on the basis of elemental (C,H,N) and spectral (IR, 1H-NMR and mass spectral data) analysis. All these compounds have also been tested for their antiinflammatory, analgesic activity and acute toxicity. Compound 4a' i.e. 2-chloro-10-[2-{3'-chloro-2'-oxo-4'-(2,6-dichloro phenyl)1'-azetidinyl} oxazol-4-yl] phenothiazine was found to possess most potent antiinflammatory activity and compound 4a i.e. 2-chloro-10-[2-{3'-chloro-2'-oxo-4'-(2, 6-dichlorophenyl) 1'-azetidinyl} thiazol-4-yl] phenothiazine showed good analgesic activity. Furthermore, these two compounds (4a and 4a') were also screened for their ulcerogenic liability.